Pendampingan Belajar Tematik Pada Santri Tingkat Sekolah Dasar Masa Pandemi Covid 19 Di Pondok Pesantren KH. Hasyim Asy’ari, Desa Banyudono, Kabupaten Ponorogo: Pendampingan Belajar Tematik Pada Santri Tingkat Sekolah Dasar Masa Pandemi Covid 19 Di Pondok Pesantren KH. Hasyim Asy’ari, Desa Banyudono, Kabupaten Ponorogo - Yafita Arfina Mu'ti; Lisma Meilia Wijayanti (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The existence of the covid-19 pandemic has caused students to study online, so school institutions use technology media as a tool in the teaching and learning process so that learning continues. In this Community Service, the service team held activities, namely thematic learning assistance which aims to help improve intellectual intelligence and enthusiasm for learning in elementary school students at Pondok Pesantren KH. Hasyim Asy'ari. The Service Team carries out learning mentoring activities using the ABCD method approach, namely (Asset Based Community Development) community service that departs from the assets or potentials of the community. In this ABCD method, there are several stages carried out including the first stage of inculturation (introduction), the second stage of discovery (disclosing information), the third design (knowing assets and identifying opportunities) and the fourth stage define (supporting the implementation of work programs), the fifth stage is reflection (reflection). With this mentoring activity, it has succeeded in helping students become more active in learning and trying to understand, seek, and find answers or materials related to thematic learning. From this it can be concluded that this learning mentoring activity is considered to have a good effect on increasing the intellectual intelligence and enthusiasm of students to learn, indicated by the increased enthusiasm for learning students, students are not easy to complain with a lot of assignments from school, increased self-confidence, responsive attitude and creativity at school students.